Analysis Financial Fisheries Business of Mackerel Scad (Decapterus macarellus) in the Southern Waters of Ambon Island - Frentje D. Silooy; Agustinus Tupamahu; O. T. S Ongkers; D. D.P Matrutty (Sangia Publishing, 2020)
This study aims 1) to determine the technical aspects of fishing with a mini purse seine; 2) to analyze the feasibility of a mini purse seine fishery business in the southern part of Ambon Island. This research was carried out from January to December 2018 in several fish landing sites scattered in the southern part of Ambon Island waters, namely Nusaniwe, Hutumuri and Lehari Villages. Sampling was by purposive sampling. Primary and secondary data were taken. Data were analyzed using descriptive analysis and business financial analysis. The dimensions of the mini purse seine vessels are 20-22.5 m long, 2.70-3.85 m wide, and 1.5-1.8 m high, the dimensions of the net are 225- 345 m long, 50-70.5 m high. The composition of the catch consisted of 4 types of fish, namely blue fly (59.8%), tuna (18.4%), skipjack (17.7%), and baby tuna (4.1%). The results showed that the mini purse seine fishery business met the requirements and was still feasible to develop. The results of the calculation of the business feasibility of a positive NPV and greater than zero (NPV> 0) of Rp. 933,471,927, an IRR of 15.8% greater than the interest rate (10.5%), the value of B / C> 1 of 1.18, the criteria for ROI of 20.14%, the value of PI (Profitability Index)> 1.